1993
DOI: 10.1136/jmg.30.10.822
|View full text |Cite
|
Sign up to set email alerts
|

Conotruncal anomaly face syndrome is associated with a deletion within chromosome 22q11.

Abstract: The conotruncal anomaly face syndrome was described in a Japanese publication in 1976 and comprises dysmorphic facial appearance and outflow tract defects of the heart. The authors subsequently noted similarities to Shprintzen syndrome and DiGeorge syndrome. Chromosome analysis in five cases did not show a deletion at high resolution, but fluorescent in situ hybridisation using probe D0832 showed a deletion within chromosome 22qll in all cases. (J Med Genet 1993;30:822-824)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
109
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(114 citation statements)
references
References 4 publications
3
109
0
2
Order By: Relevance
“…DiGeorge syndrome, 1,2 velocardiofacial syndrome (VCFS), 3 and conotruncal anomaly face syndromes, 4 and some patients with autosomal dominant Opitz G/BBB syndrome, 5,6 isolated conotruncal cardiac anomalies, 7 and Cayler cardiofacial syndrome 8 have been associated with the 22q11.2 deletion. The pattern of physical findings associated with the 22q11.2 deletion varies from patient to patient 9 and includes a conotruncal cardiac defect, palatal anomalies such as an overt cleft palate or velopharyngeal incompetence, thymic aplasia, or hypoplasia, T-cell abnormalities, and minor facial anomalies.…”
mentioning
confidence: 99%
“…DiGeorge syndrome, 1,2 velocardiofacial syndrome (VCFS), 3 and conotruncal anomaly face syndromes, 4 and some patients with autosomal dominant Opitz G/BBB syndrome, 5,6 isolated conotruncal cardiac anomalies, 7 and Cayler cardiofacial syndrome 8 have been associated with the 22q11.2 deletion. The pattern of physical findings associated with the 22q11.2 deletion varies from patient to patient 9 and includes a conotruncal cardiac defect, palatal anomalies such as an overt cleft palate or velopharyngeal incompetence, thymic aplasia, or hypoplasia, T-cell abnormalities, and minor facial anomalies.…”
mentioning
confidence: 99%
“…6 Deletions of 22q11.2 have also been detected in patients with conotruncal anomaly face syndrome and in some patients with OpitzG/ BBB and Cayler cardiofacial syndrome. [7][8][9] These disorders, collectively referred to as the 22q11.2 deletion syndrome, are predominantly characterized by congenital cardiac defects, immune deficiencies secondary to aplasia or hypoplasia of the thymus, hypocalcemia due to small or absent parathyroid glands, palatal and speech abnormalities, and cognitive difficulties. Large clinical studies and case reports have shown that the phenotypic features seen in patients with the 22q11.2 deletion are much more variable and extensive than previously recognized, and include developmental problems, feeding difficulties, neurologic, ocular, psychiatric, renal, and skeletal abnormalities.…”
mentioning
confidence: 99%
“…Resulting from a 1.5-to 3-Mb microdeletion on the long (q) arm of chromosome 22 , this disorder is most accurately characterized as the "chromosome 22q11.2 deletion syndrome" (DS22q11.2). Thus defined, the disorder encompasses previously described phenotypes including DiGeorge (1965), velocardiofacial (Shprintzen, Goldberg, Lewin, Sidoti, Berkman, Argamaso, & Young, 1978), and conotruncal anomaly face (Burn, Takao, Wilson, Cross, Momma, Wadey, Scambler, & Goodship, 1993) syndromes, and some cases of Cayler cardiofacial syndrome (Giannotti, Digilio, Marino, Mingarelli, & Dallapiccola, 1994) and Opitz G/BBB syndrome (McDonald-McGinn, Driscoll, Bason, Christensen, Lynch, Sullivan, Canning, Zavod, Quinn, & Rome, 1995). A molecular fluorescence in situ hybridization probe for the deletion set the prevalence at 1 in 4,000 live births (Burn & Goodship, 1996), an estimate currently thought to be quite conservative (e.g., Shashi, Muddasani, Santos, Berry, Kwapil, Lewandowski, & Keshavan, 2004).…”
mentioning
confidence: 99%